Tipificación de las lesiones causadas en las mujeres con sustancias químicas en la legislación ecuatoriana - Viteri Vizuete, Jessenia Carolina (2017)
This paper presents an analysis of the consequences of injuries caused to women by burns caused by the acid attack, which has generated fear and fear in this vulnerable sector of society, making it necessary to implement in the Organic Code Integral penal reforms to the norms with the purpose of hardening the sanctions, because the existing laws do not sing them as a special type of infraction and, the impact that this situation generates. Women's rights are being violated, so there is a need for coordinated and integrated political responses that reinforce the collaboration between the institutions involved in the problem and put an end to these attacks. However, it is important to highlight the governmental and non-governmental activities that are carried out to solve the problem and face its judicialization, as a way to mitigate its consequences. his is a global phenomenon that is not limited to a particular human group, regardless of religion or geographical location, these events occur continuously in countries of Southeast Asia, sub-Saharan Africa, the West Indies and the Middle East, but we also find evidence Of attacks in other regions, such as Latin America, Colombia being the country where there is a high rate of complaints about the aggression towards women with chemical substances. One of the major challenges in the fight against acid attacks in our country is to take into account certain factors that do not lead to due process, as it is: first, The lack of reports by the battered women, second, the lack of real statistics of the brutal injuries it produces; and third; The bureaucratic process to find the culprit. In the juridical analysis carried out on the facts, we can deduce that these attacks occur in their great majority, for trying to impose the male authority to the woman on the part of the man (patriarcado), it is important to mention that the fact is not denounced, for That the woman does not have a fixed job and depends on the husband and / or cohabiting partner for the maintenance of her and her children, and having no documented record, it becomes a difficult situation to proceed with the application of the law, and Not having an exact number of assaults, therefore it is not possible to have an exact number of victims in a given country or community. Therefore it is not given adequate importance and the legislation does not take into account the seriousness of these acts.